Cross-sectional and prospective associations between moderate to vigorous physical activity and sedentary time with adiposity in children - Marques, Adilson (Int J Obes (Lond), 2015)
BACKGROUND: Physical activity (PA) and sedentary time (SED) have both been suggested as potential risk factors for adiposity in children. However, there is paucity of data examining the temporal associations between these variables. OBJECTIVE: This study aimed to analyze the cross-sectional and prospective associations between PA, SED and body composition in children. METHODS: 510 children (age at baseline 10.1±0.8, age at follow up 11.8±0.9) from 6 Portuguese schools from the Oeiras Municipality participated in this study. PA and SED were measured by accelerometry and trunk fat mass (TFM) and body fat mass (BFM) were measured by Dual energy X-ray absorptiometry (DXA). Fat mass index (FMI) was calculated as BFM divided by height squared. Several regression models adjusted for age, sex, maturity status, follow-up duration, baseline levels of the outcome variable, and SED or MVPA were performed. RESULTS: Moderate to vigorous PA (MVPA) (min/d) was cross-sectionally inversely associated with adiposity indexes (FMI, TFM, BFM). Adiposity indexes were inversely associated with time in MVPA. In prospective analyses, MVPA was associated with a lower levels of FMI (β=−0.37, 95% CI: −0.49 to −0.26, p<0.001), TFM (β=−0.20, 95% CI: −0.29 to −0.10, p<0.001), and BFM (β=−0.37, 95% CI: −0.49 to −0.26, p<0.001). When the model was adjusted for age, sex, maturity status and for baseline levels of the outcome variables MVPA remained a significant predictor of lower adiposity indexes (FMI: β=−0.09, 95% CI: −0.16 to −0.01, p<0.05; TFM: β=−0.08, 95% CI: −0.15 to −0.01, p<0.05; BFM: β=−0.07, 95% CI: −0.15 to 0.00, p<0.05). Adiposity was not associated with MVPA when modeled as the exposure in prospective analyses. SED was not related with adiposity indexes, except for the relationship with FMI. CONCLUSIONS: In cross-sectional and prospective analyses, MVPA is associated with lower adiposity independent of covariates and SED. Results suggest that promoting MVPA is important for preventing gain in adiposity in healthy children.